Maldives Development Update, April 2014 - Gomez Osorio, Camilo; Abeygunawardana, Kishan; Subasinghe, Shalika; Sun, Changqing (World Bank, Washington, DC, 2014)
Real GDP growth in Maldives stood at 3.7 percent in 2013 and its outlook is positive at 4.5 percent for 2014. The tourism demand is slowly picking up and has a positive impact on growth in the non- tourism sectors. Chinese tourists continue to compensate for the weaker demand from Europe, but overall the length of stay has declined, as well as spending per tourist. Growth while dynamic was less inclusive, as the tourism industry is operating on an enclave model of development. The share of GDP from the primary sector, agriculture, mining and fisheries that employ the largest share of Maldivians in the outer atolls, was less than 0.3 percent of GDP in 2013. Loose fiscal policy in a context of moderating economic growth has led to rising macroeconomic imbalances. While revenue collection has been strong, over the past five years the gap between revenues and expenditures has widened, financed through unsustainable levels of public debt at increasing interest rates. The 2014 Budget comes with a record high envelope of MVR 17.95 billion (around 50 percent of GDP), about MVR 3 billion in new revenue measures, and an estimated 3.2 percent financing gap. Financing such high level of spending and meeting this ambitious financing gap would be difficult. Cash management will be tight through 2014. Inflation moderated to 6 percent in 2013 in 2013 although food inflation remained high.